Bimagrumab improves body composition and insulin sensitivity in insulin‐resistant individuals. Issue 1 (2nd August 2017) - Garito, Tania; Roubenoff, Ronenn; Hompesch, Marcus; Morrow, Linda; Gomez, Katherine; Rooks, Daniel; Meyers, Charles; Buchsbaum, Monte S.; Neelakantham, Srikanth; Swan, Therese; Filosa, Lee Anne; Laurent, Didier; et al.
Abstract : Aim: To test the hypothesis that an improving body composition in insulin‐resistant individuals could enhance insulin sensitivity. Methods: A total of 16 people with a mean body mass index of 29.3 kg/m 2 and insulin resistance, received a single dose of bimagrumab or placebo and were assessed at week 10 for insulin sensitivity, using a hyperinsulinaemic‐euglycaemic clamp and an intravenous glucose tolerance test (IVGTT), and for body composition using dual energy X‐ray absorptiometry and positron‐emission tomography. Results: Bimagrumab increased lean mass by 2.7% ( P  < .05) and reduced fat mass by 7.9% ( P  = .011) at week 10 compared with placebo, and had a neutral effect on body weight. Bimagrumab reduced glycated haemoglobin by 0.21% at week 18 ( P  < .001) and improved insulin sensitivity by ~20% (according to the clamp) to ~40% (according to the IVGTT). Conclusion: Taking the observed changes together, and given that these occurred without accompanying dietary intervention and without any prescribed regular physical exercise, bimagrumab may offer a novel approach for the treatment of the metabolic complications of obesity.